Corrosion monitoring

By dispersing corrosive metal nanoparticles in the electrically insulating polymer matrix, forming a conductive permeability path, and using resistance changes to detect corrosive gases, the problem of difficult to quickly respond to gas changes and detect gas composition in the prior art is solved, and rapid and continuous monitoring and sensitivity adjustment of corrosive gases are achieved.

CN119881016APending Publication Date: 2025-04-25ABB (SCHWEIZ) AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411485332.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to respond quickly to changes in ambient gases and cannot effectively detect the chemical composition or relative concentration of corrosive gases.

Method used

Using conductive ink based on metal nanoparticles, corrosive metal nanoparticles (such as silver, copper, and iron nanoparticles) are dispersed in an electrically insulating polymer matrix to form a conductive permeability path, and corrosive gases are detected by using resistance changes.

Benefits of technology

Fast and continuous monitoring of corrosive gases is achieved, information on corrosion behavior can be provided in real time, and the sensitivity of the sensor is adjusted by adjusting the material proportion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881016A_ABST
    Figure CN119881016A_ABST
Patent Text Reader

Abstract

The present disclosure relates to corrosion monitoring, and discloses a corrosion sensor comprising: corrosive metal nanoparticles dispersed in an electrically insulating polymer matrix, where an electrically conductive penetration path is formed by the corrosive metal nanoparticles in the electrically insulating polymer matrix. An increase in resistance of the corrosion sensor provides an indication of corrosion under exposure to a corrosive gas that corrodes the corrosive metal nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to corrosion monitoring and, more particularly, to corrosion sensors. Background Art

[0002] The following description of the background technology may include insights, discoveries, understandings or disclosures, or associations with disclosures that were not known to the relevant art before the present invention but that the present invention provides. Some of these contributions of the present invention may be specifically pointed out below, while other such contributions of the present invention will be apparent from their context.

[0003] Corrosion is the deterioration of metals due to chemical reactions with their environment. Corrosion of electronic components occurs in environmental conditions containing corrosive gases, which can lead to electronic component failure or electronic system failure, operational downtime and expensive repair costs.

[0004] Corrosive gases can be detected at ppb levels by indirect measurements of corroded metal panels, such as corrosion coupons (e.g., Purafil's Corrosion Grading Coupons), where an offline analytical tool is used to detect the thickness of the layer of corrosion crust that forms on top of the corroded metal panel (such as silver, copper, or iron). The thickness of the corrosion layer can then be correlated to a certain amount of corrosive gas.

[0005] In the visual inspection of the silver corrosion sensor, the silver-white color of the silver film changes with respect to the corrosive sulfur-containing gas. Due to the different diffusion rates of gases in air, the silver corrosion sensor can be used to qualitatively distinguish H by the length of the black area of ​​the corrosion sensor. 2 S gas and reduced sulfur gas (S 8 ), because H 2 S causes longer black areas due to its higher diffusion rate. The concentration of the gas is measured by silver sulfide (Ag 2 S) The length of the yellow area was qualitatively detected.

[0006] However, this slow and cumbersome offline measurement is not sufficient when it is necessary to respond to rapid changes in ambient gases. In addition, offline measurement is not suitable for detecting the chemical composition or relative concentration of corrosive gases.

[0007] For online continuous monitoring of corrosive gases, silver corrosion sensors can be used in electrical corrosion sensors, in which a thin film of silver is deposited on top of a non-corroding substrate metal. The corroded silver metal changes the resistance of the resistor network of the substrate metal and the silver film in parallel. Summary of the invention

[0008] The following briefly summarizes the features disclosed herein to provide a basic understanding of some exemplary aspects of the present invention. This summary is not an extensive overview of the present invention. It is not intended to identify the key / critical elements of the present invention, nor is it intended to describe the scope of the present invention. Its sole purpose is to present some concepts disclosed herein in a simplified form as a preface to a more detailed description.

[0009] According to an aspect, the subject matter of the independent claims is provided. Embodiments are defined in the dependent claims.

[0010] One or more embodiments will be described in more detail in the description that follows. Other features will be apparent from the description and from the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Hereinafter, the present invention will be described in more detail by way of preferred embodiments with reference to the accompanying drawings, in which

[0012] Figure 1 Test results on the sensitivity of a corrosion sensor based on printed inks are shown. DETAILED DESCRIPTION

[0013] The following embodiments are exemplary. Although the specification may refer to "one", "an" or "some" embodiments in multiple places, this does not necessarily mean that each such reference refers to the same embodiment, or that the feature applies only to a single embodiment. Individual features of different embodiments may also be combined to provide other embodiments. In addition, the words "comprise", "include" and "comprising" should be understood as not limiting the embodiments to consist only of the features mentioned, and the embodiments may also include features / structures not specifically mentioned.

[0014] Although silver is a precious metal, it may corrode in the ambient atmosphere, for example, when it is exposed to sulfur-containing gases such as hydrogen sulfide (H2S). 2 S) and / or carbon sulfide. Copper is considered a precious metal; although some air pollutants (such as H 2 S) changes its surface properties even at ambient temperature, but it remains resistant to attack by oxygen. Sulfidation of copper is a rapid process occurring at the metal-vapor interface, compromising copper's corrosion resistance and causing electrical failures in electronic devices.

[0015] Printing inks for conductive structures can be based on metal nanoparticles, where the metal nanoparticles are often stabilized with organic molecules or thiols to avoid particle agglomeration that leads to poor printability and insufficient ink stability. When metal nanoparticles are printed onto a substrate, the nanoparticles form a porous structure with a large surface area / volume ratio. The stabilizing sealant is typically removed using a thermal treatment, during which the stabilizer separates and allows the particles to move through the constriction of the bare metal surface and form a connecting interface. During the maturation process, larger particles grow at the expense of smaller particles, resulting in a thermodynamically more stable structure with a minimal surface area to volume ratio. However, even isolated metal nanoparticles form a conductive network by percolation, where the conductivity of the nanoparticle structure strongly depends on the interparticle gaps.

[0016] In embodiments, the interparticle gaps can be adjusted by introducing an excess of non-conductive polymer filler as a matrix material, thereby changing the conductivity of the metal nanoparticle network. In particular, when the interparticle distance is increased to near the percolation threshold (the point where large connected structures appear) by adding polymer, the adjustment of conductivity is expected to be large with smaller changes in interparticle distance.

[0017] The large surface area / volume ratio of nanoparticle-based conductors makes them generally sensitive to ambient gases. By avoiding high temperature sintering post-printing of metal nanoparticles that would otherwise cause significant particle growth, the metal nanoparticles are able to maintain their large surface area while being conductive and therefore suitable for gas sensor applications.

[0018] One aspect of the present invention is a corrosion sensor comprising corrosion metal nanoparticles dispersed in an electrically insulating polymer matrix, wherein a conductive permeation path is formed by the corrosion metal nanoparticles in the electrically insulating polymer matrix, wherein an increase in the resistance of the corrosion sensor under exposure to a corrosive gas that corrodes the corrosion metal nanoparticles provides an indication of corrosion. The diameter of the metal nanoparticles may be 1 to 500 nm, preferably 1 to 100 nm.

[0019] In an embodiment, the corrosion sensor may be in the form of a composite printed ink.

[0020] In an embodiment, the corrosive metal nanoparticles may be silver, copper and / or iron nanoparticles and / or any other metal nanoparticles that are susceptible to corrosion. The corrosive metal is electrically conductive.

[0021] In an embodiment, the electrically insulating polymer matrix may include polyvinyl pyrrolidone. Additionally or alternatively, the electrically insulating polymer matrix may be any electrically insulating polymer that is compatible with the metal nanoparticles. For example, dielectric polymers such as polyvinyl alcohol and / or polymethyl methacrylate may be used.

[0022] In an embodiment, the sensitivity of the corrosion sensor to the corrosive gas may depend on the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor. As the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor increases, the sensitivity of the corrosion sensor to the corrosive gas may increase. As the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor decreases, the sensitivity of the corrosion sensor to the corrosive gas may decrease.

[0023] In an embodiment, the sensitivity of the corrosion sensor to the corrosive gas may depend on the porosity of the corrosion sensor. The sensitivity of the corrosion sensor to the corrosive gas may increase as the porosity of the corrosion sensor increases. The sensitivity of the corrosion sensor to the corrosive gas may decrease as the porosity of the corrosion sensor decreases.

[0024] In an embodiment, the metal nanoparticles may be uniformly mixed in the electrically insulating polymer matrix. The encapsulated metal nanoparticles may form a percolating network within the porous structure formed by the electrically insulating polymer matrix.

[0025] In an embodiment, the corrosive gas may be SO 2 and H 2 At least one of S.

[0026] In an embodiment, the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor is from 80 / 20 to 20 / 80, preferably from 70 / 30 to 60 / 40, and more preferably 65 / 35. This means an initial weight ratio. During the use of the corrosion sensor, as the corrosion metal nanoparticles corrode when exposed to corrosive gases, the weight ratio may change, resulting in a decrease in the proportion of the corrosion metal nanoparticles in the corrosion sensor.

[0027] In an embodiment, the corrosion sensor may be used to monitor the presence of corrosive gases.The corrosion sensor may be printed on a substrate in the form of a composite printing ink.

[0028] In an embodiment, the corrosion sensor may be printed on the substrate in the form of a composite printing ink using a composite printing ink layer thickness of 0.1 to 10 μm, for example 0.5 to 1.2 μm. The layer may depend on the printing method; in flexographic printing, the layer thickness may be 0.5 to 1.2 μm.

[0029] In an embodiment, the substrate may be an electronic component. The electronic component may be at least one of a transistor, a resistor, a capacitor, a diode and / or an integrated circuit.

[0030] In an embodiment, a method for monitoring the presence of a corrosive gas is provided, the method comprising attaching a corrosion sensor to a substrate, placing the corrosion sensor in an atmosphere to be monitored, and measuring an increase in resistance in the corrosion sensor. When exposed to a corrosive gas that corrodes metal nanoparticles, an increase in the resistance of the corrosion sensor indicates the presence of a corrosive gas that corrodes the metal nanoparticles.

[0031] One embodiment provides an adjustable corrosion sensor in which corrosive metal nanoparticles are dispersed in an insulating polymer matrix. A conductive permeation path is formed by the metal nanoparticles. The corrosion sensor can be formed on a substrate using a printing method. The resistance of the sensor increases with exposure to the gas that corrodes the metal nanoparticles. The effects of corrosion may include contact between nanoparticles and changes in the proportion of conductive metal in the corrosion sensor structure. When the conductivity approaches the permeation threshold, the conductivity has a great influence on the resistance of the corrosion sensor. The corrosion sensor can be used to monitor corrosion behavior in situ. By selecting the mixing ratio of metal nanoparticles to insulating polymers, the initial conductance of the metal nanoparticle network can be customized. In addition, when using unevenly mixed polymers and metal nanoparticles, the porosity of the corrosion sensor can be adjusted and the surface area of ​​the corrosion sensor can be increased, which also affects the sensitivity of the corrosion sensor.

[0032] In an embodiment, the metal nanoparticles may be silver, copper or iron nanoparticles, preferably silver nanoparticles. When metal nanoparticles, such as silver nanoparticles, are corroded due to exposure to corrosive gases, their surfaces become non-conductive. The effective distance between the conductive nanoparticle cores increases, and if the initial inter-particle distance is close to the percolation threshold, corrosion can cause a significant change in conductivity. This can be used for corrosion sensors. In addition, when the silver nanoparticles are corroded, the proportion of conductive metal in the corrosion sensor structure decreases. The sensitivity of the metal nanoparticle-based corrosion sensor to corrosive gases can be adjusted by selecting the desired ratio of metal nanoparticles to non-conductive polymer fillers.

[0033] In an embodiment, to provide a corrosion sensor, a commercially available silver nanoparticle ink can be mixed with a polyvinyl pyrrolidone (PVP) polymer ink to form a printable composite ink. The composite ink can be printed on a polyester substrate using flexographic printing. The composite ink has a higher corrosion rate than a reference sample printed using the same silver nanoparticle ink but without a polyvinyl pyrrolidone matrix. 2 S and 1005ppb SO 2 The corrosion rate was higher in the atmosphere of 20°C (see Example 1 below).

[0034] In an embodiment, the metal nanoparticle ink and the non-conductive polymer can be uniformly mixed to form a structure in which the encapsulated metal nanoparticles form the aforementioned percolation network within the porous structure formed by the non-conductive polymer filler. By changing the mixing ratio of the metal nanoparticles to the polymer, the surface area exposed to the corrosive gas and the size of the percolation network can be changed.

[0035] One embodiment achieves low-cost, continuous monitoring of corrosive gases. The present invention achieves the corrosive gas sensor as a replaceable corrosion sensor, which can be replaced when the corrosion sensor is completely corroded or when the corrosive gas environment to be monitored changes. In addition, the sensitivity of the corrosion sensor can be adjusted by adjusting the porosity of the sensor material and the proportion of conductive metal in the sensor material.

[0036] One embodiment enables in situ corrosion measurements, which provide real-time information on corrosion behavior under operating conditions.

[0037] One embodiment enables monitoring of corrosive gases in a gas environment where the corrosion rate may vary significantly over time.

[0038] In one embodiment, an ER (resistance) probe can be used to measure the increase in resistance in a corrosion sensor. An ER probe can be used to measure the change in ohmic resistance of a corrosion sensor exposed to a corrosive gas. The effect of corrosion on the corrosion sensor causes its cross-sectional area to decrease, and the corresponding resistance to increase. The value of the increase in resistance can be directly related to the metal loss, which as a function of time is the corrosion rate. With an electrorheological probe, a direct corrosion rate can be obtained. They react quickly to corrosion disturbances and can be used to trigger an alarm. The resistance (increase) can be measured / detected using Ohm's law and providing a constant current (voltage) and measuring the voltage drop (current) across the corrosion sensor.

[0039] Example 1

[0040] A flexographic printing ink containing silver nanoparticles and a non-conductive polymer was synthesized. First, polyvinyl pyrrolidone (PVP, from Agros Organics, M W 1300k) was dissolved in isopropanol at a concentration of 30 g / l. Then, 3.3 g of Ag NP ink from InkTec (TEC-PR-040) and 2 g of isopropanol were added to 1.77 g of the previous isopropanol. The printing ink containing 65 wt% Ag NP ink and 35 wt% PVP ink was mixed thoroughly for several hours. A flexographic printing system (RKFlexiproof 100) and 10 ml / m 2The printed inks were printed in 1 or 3 layers in a row and dried at 130°C for 2 minutes to remove the solvent. No high temperature or long sintering step was performed to avoid the formation of structures with large particle sizes. The bare Ag NP ink was also printed in 1 or 3 layers as a reference. For the bare Ag NP ink printed in 1 or 3 layers, the thickness (resistance) was 0.54 μm (6.03 Ohm) and 1.12 μm (2.64 Ohm), respectively, and for the ink containing the Ag NP / PVP mixture, the thickness (resistance) was 0.57 μm (33.65 Ohm) and 1.00 μm (38.98 Ohm), respectively. The resistance of the silver nanoparticle / polyvinyl pyrrolidone monolayer mixture varied greatly (deviation of about 40%). SEM images show that the printed ink layer is porous and the silver nanoparticles show a certain degree of shrinkage, but no large particles are formed.

[0041] The printed Ag NP and Ag NP / PVP traces were exposed to the corrosive gas H at a relative humidity of 80%. 2 S (1005 ppb) and SO 2 (1005ppb). During the 40-day test period, the resistance of the Ag NP ink as 3 layers did not show an increase in resistance, while the resistance of the samples with 1 layer of Ag NP and 3 layers of Ag NP / PVP showed an increase of about 25%. In addition, the resistance of the silver nanoparticle / polyvinyl pyrrolidone single layer printed sample has increased by more than 90%, indicating a high sensitivity to corrosive gases. The test results are shown in Figure 1 The results show that the sensitivity of the corrosion sensor can be tuned by controlling the amount of corrosion-promoting metal nanoparticles in the insulating polymer matrix.

[0042] It is obvious to a person skilled in the art that, as technology advances, the inventive concept can be implemented in many ways.The invention and its embodiments are not limited to the examples described above but may vary within the scope of the claims.

Claims

1. A corrosion sensor comprising: corrosion metal nanoparticles dispersed in an electrically insulating polymer matrix, wherein an electrically conductive percolation path is formed by the corrosion metal nanoparticles in the electrically insulating polymer matrix, Wherein an increase in the resistance of the corrosion sensor when exposed to a corrosive gas that corrodes the corrosive metal nanoparticles provides an indication of corrosion.

2. The corrosion sensor according to claim 1, wherein the corrosion sensor is in the form of a composite printing ink.

3. The corrosion sensor according to claim 1 or 2, wherein the corrosion metal nanoparticles are silver, copper and / or iron nanoparticles and / or other metal nanoparticles.

4. A corrosion sensor according to claim 1, 2 or 3, wherein the electrically insulating polymer matrix comprises polyvinyl pyrrolidone, polyvinyl alcohol and / or poly(methyl methacrylate).

5. The corrosion sensor according to any one of the preceding claims, wherein the sensitivity of the corrosion sensor to the corrosive gas depends on the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor, wherein the sensitivity of the corrosion sensor to the corrosive gas increases as the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor increases, The sensitivity of the corrosion sensor to the corrosive gas decreases as the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor decreases.

6. The corrosion sensor according to any one of the preceding claims, wherein the sensitivity of the corrosion sensor to the corrosive gas depends on the porosity of the corrosion sensor, wherein the sensitivity of the corrosion sensor to the corrosive gas increases as the porosity of the corrosion sensor increases, The sensitivity of the corrosion sensor to the corrosive gas decreases as the porosity of the corrosion sensor decreases.

7. The corrosion sensor according to any one of the preceding claims, wherein the metal nanoparticles are unevenly mixed in the electrically insulating polymer matrix, wherein the encapsulated metal nanoparticles form a percolating network within a porous structure formed by the electrically insulating polymer matrix.

8. The corrosion sensor according to any one of the preceding claims, wherein the corrosive gas is at least one of SO2 and H2S.

9. The corrosion sensor according to any one of the preceding claims, wherein the weight ratio of the corrosion metal nanoparticles to the electrically insulating polymer matrix in the corrosion sensor is from 80 / 20 to 20 / 80, preferably from 70 / 30 to 60 / 40, more preferably 65 / 35.

10. Use of a corrosion sensor according to any one of claims 1 to 9 for monitoring the presence of corrosive gases, wherein the corrosion sensor is printed on a substrate in the form of a composite printing ink.

11. Use according to claim 10, wherein the corrosion sensor is printed on the substrate in the form of a composite printing ink with a composite printing ink layer thickness of 0.1 to 10 μm, such as 0.5 to 1.2 μm.

12. The use according to claim 10 or 11, wherein the substrate is an electronic component.

13. A method for monitoring the presence of corrosive gases, the method comprising: A corrosion sensor according to any one of claims 1 to 9 is attached to a substrate, placed in an atmosphere to be monitored, and an increase in resistance in the corrosion sensor is measured.